Malaysian postmodern art and its strategies - Abdullah, Sarena (Nanyang Academy of Fine Arts, 2008)
Since the the 1990s. there has emerged a plural tendency in Malaysian arts practices. A new breed of young artists had discarded the pursuit of national identity despite the implementation of and emphasis on the Malay-Islamic based cultural preferences endorsed by the Malaysian government. Art works produced began to become more diverse. Multi-dimensional art forms such as installations and performances, and electronic media such as video and cameras began to be used. Works about non-Malay cultures and different lifestyles began to be exhibited in the National Art Gallery (NAG) and entered into the Young Contemporary Awards (Bakat Seni Sezaman). These outlooks can be discussed, and have been suggested, to be postmodern as they are almost parallel in time line, or have the outlook of Western postmodern art. These past modern outlooks. or rather the plurality of Malaysian art, however, are not new. Redza Piyadasa, in discussing Malaysian art development in Malaysia argues that there were a few postmodernist in the mid 1970s and one of them was an exhibition emitted "Towards a Mystical Reality" This paper will discuss three postmodern an strategies in Malaysia, conceptualised through "Towards a Mystical Reality," allegory and appropriation.